Energy transitions, regulatory and policy trends - Mersinia, Ioanna; Penttinen, Sirja-Leena (ELRF collection, 2017)
Energy Transitions: Regulatory and Policy Trends highlights the recent developments in EU energy law and underlying policy aspects that shape the regulatory approach to energy. By acknowledging the multidisciplinary nature of energy law, its close relationship with policy issues and its development as an evolving new sector-specific legal field, this book reflects the multifaceted nature of EU energy law by focusing on the most topical issues of EU energy law and policy today. It examines regulatory and institutional developments in EU energy law, the case law of the Court of Justice in the field of energy, and different policy dimensions and external aspects of EU energy law. The themes covered include: capacity mechanisms, interactions between EU and international organisations and jurisdictions outside the EU, application of general EU law to the energy sector, sustainability aspects such as the current state of renewable energy support schemes and waste-to-energy processes, underground gas storage facilities, and various aspects of shale gas developments in the EU. Energy Transitions: Regulatory and Policy Trends is of importance for academics and students as well as practitioners and policy makers working in the field of energy law. ...